Reinterpreting Ḥifẓ al-nasl in Contemporary Marriage Contracts: Navigating Islamic Normativity and State Law - Mustamam; Danialsyah; Nurasiah Harahap; Mega Arum Saputri; Lutter Ariestino (Faculty of Sharia, IAIN Metro, 2025)
This study aims to reinterpret the concept of ḥifẓ al-nasl (protection of lineage) within contemporary marriage contracts in Indonesia by examining the relationship between the normative framework of Islamic law and the state legal system. Traditionally, ḥifẓ al-nasl, as one of the primary objectives of Islamic law (maqāṣid al-sharī’ah), emphasizes the preservation of lineage legitimacy through the institution of marriage. However, in the modern Indonesian socio-legal context—characterized by a dual legal system of religious law and state law—its implementation reflects a dynamic interplay between these frameworks. This research employs a qualitative approach, including field studies at several Offices of Religious Affairs (Kantor Urusan Agama or KUA), in-depth interviews with marriage registrars (penghulu), religious leaders, and married couples, as well as an analysis of marriage contract documents. The findings reveal a shift in the meaning of ḥifẓ al-nasl, which is no longer understood solely in terms of lineage legitimacy but also encompasses the protection of reproductive rights, family planning, and legal certainty within marriage contracts. These findings indicate that, while Islamic normative values remain a foundational reference, the application of state law in Indonesia—particularly through the legalization of marriage contracts and state oversight—has contributed to a new interpretation of the principle of ḥifẓ al-nasl. The study recommends strengthening the integration between maqāṣid al-sharī’ah and the positive legal system in formulating marriage policies that are adaptive and responsive to contemporary challenges. The academic contribution of this research lies in offering a new conceptual framework for contextually understanding ḥifẓ al-nasl, one that integrates the objectives of Islamic law with Indonesia’s positive legal system.